2002
DOI: 10.1007/s00417-002-0452-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of mycophenolate mofetil on cultured human Tenon fibroblasts

Abstract: MMF has a concentration-dependent antiproliferative effect on HTF without any detected cytotoxicity in the applied concentration range. Brief incubation also leads to a growth arrest; therefore, intraoperative MMF application might prevent exaggerated scarring after glaucoma filtering surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…Similar to mPRED, MMF caused a significant inhibition of cell proliferation, and this is in line with previously published in vitro data [39,43,44]. The concentration of 1 mg?L -1 MMF corresponds to the target whole-blood level for transplant patients [45].…”
Section: Figuresupporting
confidence: 77%
“…Similar to mPRED, MMF caused a significant inhibition of cell proliferation, and this is in line with previously published in vitro data [39,43,44]. The concentration of 1 mg?L -1 MMF corresponds to the target whole-blood level for transplant patients [45].…”
Section: Figuresupporting
confidence: 77%
“…MPA leads to a five times more effective inhibition of IMPDH type II, which is mainly expressed in activated lymphocytes, but it also inhibits the type I isoform expressed in most other cell types [16] . This may also cause a dose-dependent inhibition of fibroblast proliferation, as has been shown in rat kidneys [17] , cultures of human Tenon cells of the eye [18] as well as in dermal fibroblast cultures [19] . A group from Heidelberg reported recently that MPA administration to cultured human fibroblasts resulted in a downregulation of cytoskeletal proteins, a rearrangement of the cytoskeleton and impaired migrational capacity.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro studies showed that MPA has a direct antiproliferative effect and inhibits cell activation in cultures of mesangial cells, the fibrogenic cells within glomeruli [11,12]. Other studies report that MPA is able to inhibit the proliferation of tenon fibroblasts and vascular smooth muscle cells, which are main players in fibrotic processes in the eye and during atherosclerosis, respectively, [13,14]. This may imply that MPA can also act on HSC.…”
Section: Introductionmentioning
confidence: 92%